The Benefit of Films in Nursing Education: A Rapid Review - Adiningsih, Berthy Sri Utami; Saifudin, I Made Moh. Yanuar; Fradianto, Ikbal (Indonesian Journal of Global Health Research, 2024)
Traditional teaching methods in health education often emphasize cognitive aspects. Cinemeducation is non-traditional learning method that using film that has been used recently in medical education to enhance psychosocial skills, but less explored in nursing education. This study aims to evaluate the benefits of using films as a learning tool, especially for nursing education. A rapid review methodology was employed following the PRISMA guidelines. The review covered papers published between 2018 and 2024, focusing on healthcare students particularly in nursing and medicine. Consensus App and ResearchGate databases were searched with terms “"film OR movie AND nursing education" and "cinemeducation OR cinenurducation". 91.792 studies were identified, six were included with two of them exclusively focus on nursing. All studies found that films increased students’ enthusiasm, promoting active learning and have considerably impact on development of psychosocial abilities such as professionalism, ethics and communication. Cognitive improvement also noticed, notably in comprehending complicated bioethical concepts and psychological circumtances. Cinenurducation is a valuable strategy to improve both cognitive and affective learning outcomes in nursing education. While promising, it should be combined with other teaching methods to optimize learning outcomes.